Determinación de Protocolos de Medición de Contaminantes producto de la Combustión en vehículos a gasolina en la Ciudad de Salcedo, periodo 2019 – 2020. - Arias Gualpa, Karolina Elizabeth (2020)
The present investigation aims to determine the measurement protocols for polluting gases generated by the combustion of gasoline vehicles in the city of Salcedo, the investigation ended up diagnosing the levels of opacity that harm the environment due to excess emissions of the gases of the vehicles during their combustion process, which constitute one of the main causes of deterioration in air quality, affecting human health and being responsible for global warming, the factors involved in the measurement of polluting gases were analyzed of the automotive fleet in the city of Salcedo, in order to identify the atmospheric pollutants with the greatest impact of environmental pollution. Through the investigation, measurement protocols were generated for the AVL DITEST CDS 450 equipment, together with the help of the AVL DITEST GAS 1000 equipment that allows analyzing the emission of carbon monoxide (CO) and unburned hydrocarbons (HC), for the evaluation of the automotive, the measurement protocol established by the Ecuadorian Technical Regulation NTE INEN 2204: 2002 was used, where it was identified that there is greater contamination by unburned hydrocarbons (HC), with 41.64% of vehicles that do not comply with the Technical Regulation Ecuadorian. Through the results and information obtained, strategies were carried out to reduce the emission of pollutants generated by the gasoline-powered fleet in the city of Salcedo.